(untitled) (Bangladesh Agronomy Journal, 2023)
The field experiment was conducted at Agronomy Research Field, BARI, Gazipur during kharif-1 season of 2020 and 2021 to find out suitable combination of maize and dwarf yard long bean intercropping for higher productivity and monetary advantage. Treatments included in the experiment were: T1= Maize normal row (MNR) +1 row dwarf yard long bean (DYLB), T2= Maize paired row (MPR) + 2 rows DYLB, T3= MPR +3 rows DYLB, T4= MPR + 4 rows DYLB, T5= Sole maize (60 cm x 20 cm) and T6= Sole DYLB (40 cm x 25 cm). Light availability on DYLB decreased with the increase of shade produced by maize canopy over the time up to 105 DAS. The lowest light availability on DYLB was observed in T1 treatment and the highest light availability in sole DYLB (T6). The maximum grain yield of maize was observed in sole maize decreased by 1-4 % among the intercrop treatments. The highest maize equivalent yield (13.75 t ha-1), gross return (Tk. 247500 ha-1), gross margin (Tk. 139000 ha-1) and benefit cost ratio (2.28) were observed inT3 followed by T1. The highest land equivalent ratio (1.56) was also found in the same treatment. The results revealed that maize paired row + 3 rows dwarf yard long bean and hybrid maize normal row (60cm x 20cm) + 1 row dwarf yard long bean might be agronomically feasible and economically profitable for maize and dwarf yard long bean intercropping system at Joydebpur. Bangladesh Agron. J. 2022, 25(2): 11-17